Stimulation of convicts’ law-abiding behaviour as a principle of punishments execution in France - Puzyrev, Mikhail (Journal of the Belarusian State University. Law, 2019)
The article deals with implementation of the principle of stimulation of convicts’ law-abiding behaviour in France compared to corresponding provisions of the criminal-executive legislation of Ukraine. The author established that the implementation of the principle of stimulation of convicts’ law-abiding behaviour in France is realized through the use of such promotional institutions of criminal-executive law as measures of encouraging, parole, reduced sentence. Comparative analysis of the legislation of France regarding the use of measures of encouraging concerning convicts to imprisonment with the provisions of the domestic criminal-executive legislation (article 130 of the Criminal-Executive Code of Ukraine) revealed that in this aspect the Ukrainian penitentiary legislation is more humane, because measures of encouraging provided by the French legislation correspond to the appropriate convicts’ rights according to the Criminal-Executive Code of Ukraine. The author carried out such distinctive features of using parole in France compared to Ukraine: the smaller degree of differentiation of the formal grounds; not detailed definition of the material ground; the wider volume of duties that may be assigned to parolee.
Keywords: comparative studies in the field of the criminal-executive law; stimulation of convicts’ law-abiding behaviour; principles of punishments execution; foreign experience